2008
DOI: 10.1149/1.2981148
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric Sensors for Detection of Elemental Mercury Vapor

Abstract: Several organic and inorganic materials have been tested for possible incorporation into a sensing array in order to add elemental mercury vapor to the suite of chemical species detected. Materials have included gold films, treated gold films, polymer-carbon composite films, gold-polymer-carbon composite films and palladium chloride sintered films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, in rare circumstances when these spectroscopic methods are utilized for online monitoring, they tend to be extremely costly and require logistical and skilled personnel to maintain the system. To overcome these shortfalls, there has been numerous studies on developing Hg 0 vapor sensors, most of which are based on surface plasmon resonance (SPR) and microsensors such as quartz crystal microbalance (QCM), surface acoustic wave (SAW), , and conductometric. Most of these developed Hg 0 vapor sensors are based on Au-thin film or Au-based nanomaterials where mass or conductivity of the sensing surface changes due to Hg–Au amalgamation. Among the microsensors, conductometric devices have gained huge interest for Hg 0 vapor sensing due to their simple operating mechanism and fabrication procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in rare circumstances when these spectroscopic methods are utilized for online monitoring, they tend to be extremely costly and require logistical and skilled personnel to maintain the system. To overcome these shortfalls, there has been numerous studies on developing Hg 0 vapor sensors, most of which are based on surface plasmon resonance (SPR) and microsensors such as quartz crystal microbalance (QCM), surface acoustic wave (SAW), , and conductometric. Most of these developed Hg 0 vapor sensors are based on Au-thin film or Au-based nanomaterials where mass or conductivity of the sensing surface changes due to Hg–Au amalgamation. Among the microsensors, conductometric devices have gained huge interest for Hg 0 vapor sensing due to their simple operating mechanism and fabrication procedure.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that surfactants (i.e., hexadecanethiol) and novel nanomaterials (i.e., Au nanowires, carbon nanotubes and polymer-carbon composites) can be utilized to enhance the sensitivity an selectivity of conductometric based Hg 0 vapor sensors. , However, in most cases, the selectivity performance of those sensors toward low concentrations of Hg 0 vapor in the presence of common interfering gas species present in industrial effluent stacks has not been addressed and thereby their potential use in industrial stack effluents are still in question. In fact, a carbon nanotube based conductometric sensor developed by McNicholas et al (2011) was shown to have almost similar response magnitudes toward Hg 0 and toward H 2 S vapor.…”
Section: Introductionmentioning
confidence: 99%